Nonconsensual Sexual Experience Acknowledgment: Exploring the Roles of Gender Identity, Sexual Aggression Myths, and Psychological Inflexibility - Wesley Malvini; Jessica M. Criddle; Mark S. Lacour; Emily K. Sandoz (Behavioral Sciences, 2025)
Nonconsensual sexual experiences (NSEs) can take many forms, including rape and sexual assault. NSE acknowledgment has been linked to several positive and negative outcomes. A person’s acknowledgment of their NSEs may be in part due to the extent to which they accept myths about sexual aggression (AMASA). However, AMASA does not fully account for NSE acknowledgment, which necessitates research on possible moderators. Further, other individual differences, such as gender identity, may play a role in both AMASA and acknowledgment. The primary aim of this study was to examine psychological flexibility (PF) and inflexibility (PI) as potential moderators of the relationship between NSE acknowledgment and AMASA. AMASA and gender identity both had significant, positive associations with acknowledgment. Furthermore, there was a significant negative relationship between acknowledgment and PI. The current study provides data on two psychological constructs that may serve as target areas for developing interventions to support people with NSE histories, as well as furthering our understanding of acknowledgment across gender identities.